Low temperature thermochronology in the Eastern Alps: Implications for structural and topographic evolution - Wolfler, A.; Stuwe, K.; Danisik, M.; Evans, Noreen (Elsevier Science BV, 2012)
According to new apatite fission track, zircon- and apatite (U–Th)/He data, we constrain the near-surface history of the southeastern Tauern Window and adjacent Austrolapine units. The multi-system thermochronological data demonstrate that age-elevation correlations may lead to false implications about exhumation and cooling in the upper crust. We suggest that isothermal warping in the Penninic units that are in the position of a footwall, is due to uplift, erosion and the buildup of topography. Additionally we propose that exhumation rates in the Penninic units did not increase during the Middle Miocene, thus during the time of lateral extrusion. In contrast, exhumation rates of the Austroalpine hangingwall did increase from the Paleogene to the Neogene and the isotherms in this unit were not warped. The new zircon (U–Th)/He ages as well as zircon fission track ages from the literature document a Middle Miocene exhumation pulse which correlates with a period of enhanced sediment accumulation during that time. However, enhanced sedimentation- and exhumation rates at the Miocene/Pliocene boundary, as observed in the Western- and Central Alps, cannot be observed in the Eastern Alps. This contradicts a climatic trigger for surface uplift, and makes a tectonic trigger and/or deep-seated mechanism more obvious to explain surface uplift in the Eastern Alps.In combination with already published geochronological ages, our new data demonstrate Oligocene to Late Miocene fault activity along the Möll valley fault that constitutes a major shear zone in the Eastern Alps. In this context we suggest a geometrical and temporal relationship of the Katschberg-, Polinik–Möll valley- and Mur–Mürz faults that define the extruding wedge in the eastern part of the Eastern Alps. Equal deformation- and fission track cooling ages along the Katschberg–Brenner- and Simplon normal faults demonstrate overall Middle Miocene extension in the whole alpine arc.